SEJARAH DUSUN EMPELU DALAM PELASTARIAN BUDAYA BALAYIE 2010-2023 - Hadial Azizi; Zulfa; Juliandry Kurniawan Junaidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the history of Empelu Hamlet in the preservation of Balayie culture from 2010 to 2023. The background of this study stems from the fading tradition of Balayie, a ritual of the Empelu Hamlet community in Bungo Regency, Jambi, which has long been performed as a form of prayer to ask for rain during long dry seasons. This situation became an important issue that prompted research on how the people of Empelu Hamlet sought to preserve Balayie between 2010 and 2023. This research uses the historical method, which consists of four stages, namely: (1) heuristics, namely the collection of primary sources in the form of interviews with traditional leaders, hamlet heads, and the Empelu community, as well as secondary sources in the form of archives, documents, articles, and journals; (2) source criticism, both external and internal, to ensure the authenticity and validity of the data; (3) interpretation, which is the interpretation of historical facts to obtain meaning and relationships between events; and (4) historiography, which is writing the results of research in the form of a coherent, systematic, and understandable historical narrative. The results of the research show that the Balayie tradition has long historical roots and is closely related to the life of the community in Empelu. In the past, Balayie was performed in a sacred manner by traditional elders using boats on the Batang Tebo River while chanting poems and prayers. In 2023, Balayie was revived through the Kenduri Swa event. In the past, Balayie was performed in a sacred manner by traditional elders using canoes on the Batang Tebo River while chanting poems and prayers. In 2023, Balayie was revived through the Kenduri Swarnabhumi event held in Lubuk Sakti. Traditional shops, the younger generation, the local government, and the Ministry of Education, Culture, Research, and Technology demonstrated their synergy in cultural revitalization efforts.